2022
DOI: 10.3390/jof8050501
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy and Phylogeny of Meruliaceae with Descriptions of Two New Species from China

Abstract: Two new wood-inhabiting fungi Hermanssonia fimbriata sp. nov. and Phlebia austroasiana sp. nov. in the Meruliaceae family are described and illustrated from southwestern China based on molecular and morphological evidence. The characteristics of H. fimbriata include annual, resupinate basidiomata, the absence of cystidia and cystidioles, oblong ellipsoid basidiospores of 5–6 × 2.4–3 μm, and growth on rotten gymnosperm wood in the east Himalayas. Its basidiomata change drastically upon drying, from being a ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“… Aurantiporus is found to be highly polyphyletic in the family Meruliaceae , as shown in our phylogenetic analysis as well as in previous studies ( Floudas and Hibbett 2015 ; Chen et al 2021 ; Liu et al 2022 ). The type species of Aurantiporus was erected by Murrill (1905) as Polyporus pilotae Schwein.…”
Section: Discussionsupporting
confidence: 91%
“… Aurantiporus is found to be highly polyphyletic in the family Meruliaceae , as shown in our phylogenetic analysis as well as in previous studies ( Floudas and Hibbett 2015 ; Chen et al 2021 ; Liu et al 2022 ). The type species of Aurantiporus was erected by Murrill (1905) as Polyporus pilotae Schwein.…”
Section: Discussionsupporting
confidence: 91%
“…Apart from these bacteria, the fungi, e.g., Meruliaceae and Pleosporaceae, showed similar trends. Members of Meruliaceae were the most influenced by multiple environmental parameters, three OTUs associated with Meruliaceae showed positive relationships with the bioavailable Fe, Ni, and V. Although Meruliaceae often grows on rotten gymnosperm wood (Liu et al, 2022e), the relationship of Meruliaceae with metal(loid)s has not been studied. Additionally, two OTUs associated with Pleosporaceae showed positive relationships with the bioavailable Fe and V. It was consistent with the observation of rhizosphere fungal communities in a Cu tailings area (Jia et al, 2020).…”
Section: Effects Of Geochemical Characteristics On Bacterial and Fung...mentioning
confidence: 99%
“…With the addition of molecular data to taxonomic and systematic studies, many new genera have been introduced or resurrected to accommodate some species from Phlebia s.l. (i.e., Allophlebia, Cabalodontia, Crustodontia, Geesterania, Hermanssonia, Lilaceophlebia, Mycoacia, Mycoaciella, Phlebiopsis, Scopuloides and Resinicium) (Floudas & Hibbett, 2015;Papp & Dima, 2017;Westphalen et al, 2018Westphalen et al, , 2021Lira et al, 2022;Liu et al, 2022;among others). Recently, Chen et al (2021) provided a wide overview of the Phlebioid clade and the Meruliaceae, and showed that Phlebia s.l.…”
Section: Introductionmentioning
confidence: 99%